Model analysis of electroflotation water treatment of wastewater containing microplastics - Ksenofontov Boris Semenovich; Bondarenko Anna Viktorovna; Rusanova Kristina Rodionovna (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
The paper presents a model of the microplastic electroflotation process and considers the factors affecting the efficiency of this process during wastewater treatment. The results obtained will help optimize the microplastic electroflotation process and develop more effective ways to remove plastic particles from the treated water, as well as help in the development of new types of flotation technology that allow several purification processes to be carried out simultaneously in one device. These devices can prevent the destruction of the formed flotation complexes, compared with the use of a traditional cleaning scheme with several autonomous devices installed in series. The results obtained provide a rationale for choosing the most efficient electroflotation apparatus for wastewater treatment from microplastics.